Penn Medicine Head and Neck Cancer Service Line COVID‐19 management guidelines. Issue 7 (25th June 2020) - Weinstein, Gregory S.; Cohen, Roger; Lin, Alexander; O'Malley, Bert W.; Lukens, John; Swisher‐McClure, Samuel; Shanti, Rabie M.; Newman, Jason G.; Parhar, Harman S.; Tasche, Kendall; Brody, Robert M.; Chalian, Ara; et al.
Abstract: Introduction: The COVID‐19 pandemic caused by the severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) virus has altered the health care environment for the management of head and neck cancers. The purpose of these guidelines is to provide direction during the pandemic for rational Head and Neck Cancer management in order to achieve a medically and ethically appropriate balance of risks and benefits. Methods: Creation of consensus document. Results: The process yielded a consensus statement among a wide range of practitioners involved in the management of patients with head and neck cancer in a multihospital tertiary care health system. Conclusions: These guidelines support an ethical approach for the management of head and neck cancers during the COVID‐19 epidemic consistent with both the local standard of care as well as the head and neck oncological literature.